Tourist’s perception of the sustainable development of the Machalilla National Park - López Vera, Boris Miguel; Indacochea Ganchozo, Blanca Soledad; Falconí Yépez, Pedro Segundo (Revista Venezolana de Gerencia, 2023)
The Machalilla National Park (MNP) has included, as a tourism development strategy, the use of its the extensive compendium of tourism resources, however, this uncontrolled use in the integration of tourism activities can generate environmental deterioration and thus, a decline in the arrival of tourists. The objective of this research is to analyze tourists’ perception in the sustainable development of the Machalilla National Park. The methodology used to reach this objective was of a mixed descriptive type with a documental and bibliografic design. The results related to tourist’s sociodemographic profile highlighted that the vast majority of tourists that arrives at the MNP are conformed by: women, ages 22-31, they are national, coming from Manabi province, students, visiting this place for touristic pourposes. Regarding tourist potential areas, this study determined that Playa Los Frailes was the place with the greates tourist influx during the peirod May-August. The main weaknesses detected were the environmental aspect, high number of tourists and garbage, specifically plastic garbage. In conclusion, it is transcendental to strengthen the processes and activities of the management of the MNP to ensure the environmental sustainability of its natural, cultural and social values.